Exploring NoC jitter effect on simulation of spiking neural networks - Sergei Dytckov; Sushri Sunita Purohit; Masoud Daneshtalab; Juha Plosila; Hannu Tenhunen (My University, 2022)
The major bottleneck in simulation of large-scale neural networks is the communication problem due to one-to-many neuron connectivity. Network-on-Chip concept has been proposed to address the problem. This work explores the drawback that is introduced by interconnection networks – a delay jitter. The preliminary experiment is held in the spiking neural network simulator introducing variable communicational delay to the simulation. The performance degradation is reported.
Proceedings of the 2014 International Conference on High Performance Computing & Simulation (HPCS 2014)